Influence of convection drying with hot air on the physicochemical and phytochemical properties of green banana flour (Musa cavendish) - Espinoza-Espinoza, Luis Alfredo; Juárez-Ojeda, Carlos Eduardo; Ruiz-Flores, Luis Alberto; Moreno-Quispe, Luz Arelis; Anaya-Palacios, Mirtha Susana; Cárdenas-Quintana, Haydée (Frontiers in Sustainable Food Systems, 2023)
The present study focuses on the effect of different drying temperatures (DT) (40, 60 and 80 ºC) and the combination of banana slice thicknesses (BST) (2 and 4 mm) on the physicochemical properties and phytochemicals of green banana flour (GBF). The influence of the drying temperature and thickness of the banana pulp slice were significant (p<0.05) on the TPC and % inhibition of the DPPH radical. As the temperature increased from 60 to 80 ºC and the thickness decreased from 4 to 2 mm, the TPC values (225.69 ± 5.13 GAE/100 g DW) and % inhibition of the DPPH radical (91.08 ± 2.28%) were higher, respectively. Physicochemical properties such as: soluble solids, titratable acidity, pH and ashes were not influenced by DT and BST; and the humidity values were <10%. These findings indicate that drying with hot air from 60 to 80 °C and thicknesses < 4mm favor a greater conservation of the antioxidant capacity in banana flour.